Neuroleptic malignant syndrome: another medical cause of acute abdomen. Issue 767 (September 1989) - Lo, T. C.; Unwin, M. R.; Dymock, I. W.
Abstract : We present a patient with neuroleptic malignant syndrome and intestinal pseudo-obstruction misdiagnosed as being secondary to septicaemia. The management of the patient is discussed with emphasis on the role of creatine kinase and liver function tests.